Stable and discriminating radiomic predictor of recurrence in early stage non-small cell lung cancer: Multi-site study. (April 2020) - Khorrami, Mohammadhadi; Bera, Kaustav; Leo, Patrick; Vaidya, Pranjal; Patil, Pradnya; Thawani, Rajat; Velu, Priya; Rajiah, Prabhakar; Alilou, Mehdi; Choi, Humberto; Feldman, Michael D.; Gilkeson, Robert C.; et al.
Highlights: Surgery is a potentially curative treatment modality for early-stage NSCLC. Despite the curative intent of therapy, about 40–55 % of NSCLC develop recurrence. There is no consensus regarding the use of histologic markers about adjuvant therapy. There is no non-invasive biomarker to identify cancer recurrence post-surgery. Stable and discriminate radiomic features can predict cancer recurrence post-surgery. Abstract: Objectives: To evaluate whether combining stability and discriminability criteria in building radiomic classifiers will improve the prognosis of cancer recurrence in early stage non-small cell lung cancer on non-contrast computer tomography (CT). Materials and Methods: CT scans of 610 patients with early stage (IA, IB, IIA) NSCLC from four independent cohorts were evaluated. A total of 350 patients from Cleveland Clinic Foundation and University of Pennsylvania were divided into two equal sets for training (D1 ) and validation set (D2 ). 80 patients from The Cancer Genome Atlas Lung Adenocarcinoma and Squamous Cell Carcinoma and 195 patients from The Cancer Imaging Archive, were used as independent second (D3 ) and third (D4 ) validation sets. A linear discriminant analysis (LDA) classifier was built based on the most stable and discriminate features. In addition, a radiomic risk score (RRS) was generated by using least absolute shrinkage and selection operator, Cox regression model to predict time to progression (TTP) following surgery. Results: A feature selection strategy focusing on both feature discriminability and stability resulted in the classifier having a higher discriminability on validation datasets compared to the discriminability alone criteria in discriminating cancer recurrence (D2, AUC of 0.75 vs. 0.65; D3, 0.74 vs. 0.62; D4, 0.76 vs. 0.63). The RRS generated by most stable-discriminating features was significantly associated with TTP compared to discriminating alone criteria (HR = 1.66, C-index of 0.72 vs. HR = 1.04, C-index of 0.62). Conclusion: Accounting for both stability and discriminability yielded a more generalizable classifier for predicting cancer recurrence and TTP in early stage NSCLC.